Thermal analysis of molten salts and their mixtures with metals - D Sergeev; J Qi; S Gezgin; D Rapp; A Lichtinger; F Beckstein; M Müller (The Australasian Institute of Mining and Metallurgy, 2024)
Salts and their mixtures play an important role for industrial and energy sectors, eg metallurgy, biomass gasification and combustion, nuclear and solar powerplants and electrochemical processes. Depending on the composition of salts (eg Li+, Na+, K+, Mg2+, Ca2+ // NO3-, F-, Cl-, CO32-, SO42-, etc), the temperature range for different applications can vary starting from room temperature and going up to 1500°C. For the proper design and modelling of heat exchangers and other equipment, it is necessary to have reliable and validated data sets of thermophysical properties. The 50 mol per cent NaNO3 – 50 mol per cent KNO3 salt mixture as a well-studied composition was selected for validation of relevant thermophysical properties (heat capacity, enthalpy of phase transitions, thermal expansion, viscosity and thermal conductivity). To study these properties of the liquid phase, special crucibles and approaches should be implemented. Verification of these crucibles for different methods (differential scanning calorimetry (DSC), thermomechanical analysis (TMA), laser flash analysis (LFA) and rheometers) has been performed. The low thermal conductivity of salts is one of the main problems in implementing latent heat storage. In this project, the authors intend to develop a fundamental solution to this problem using chemically bonded metals with salts. These are known as metal-salt solutions. To fit the main parameters of new phase change materials to the requirements of thermal energy storage, a wide variety of possible combinations should be considered. CALPHAD modelling is used together with thermal analysis for the development of a consistent thermodynamic database including chloride salts (Li, Na, K, Mg, Ca // Cl) and corresponding metals (Li, Na, K, Mg, Ca). The results of the study of quasibinary and multicomponent metal-salt (eg Mg-KCl and Ca-KCl) systems as well as the selection of suitable crucible materials and challenges by studying of these systems will be discussed.